Pengalaman Dilema Etik Bagi Perawat di Ruang Intensive Care Unit - Sri Wulan Megawati; Anastasia Anna (STIKes Karsa Husada Garut, 2018)
Nurses in Intensive Care (ICU) often face ethical dilemmas. They often face problems that require consideration of ethics in everyday practice. Advances in technology and consumer demand for high-quality services can put a nurse in a condition that causes a dilemma. The purpose of this research paper is to find out how ICU nurses experience in dealing with ethical dilemmas. The data collected in the form of publication of the journal literature, traced by-CINALHL EBSCOhost, ProQuest, PubMed, HealthMed Journal etc. by using the keyword